Pelaksanaan Pengawasan dan Pembinaan Pembiayaan Murabahah Bermasalah di KSPPS BMT Husnul Aulia Ciledug - siti fatimah; Toto Suharto (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2020)
This study aims to determine the implementation of supervision and fostering problematic murabaha financing at BMT Husnul Aulia Ciledug.This study uses qualitative research with data collection methods using interviews, observation and documentation and then analyzed using descriptive analysis.The results of this study: the implementation of preventive supervision of murabaha financing in BMT Husnul Aulia namely by carrying out administrative supervision namely checking all required documents and applying the principle of 6C in the analysis of financing, while the implementation of repressive supervision of murabaha financing is problematic by carrying out direct supervision of visiting places businesses of BMT members routinely and carry out indirect supervision, namely nominative checks. In addition to supervision, BMT Husnul Aulia conducts coaching that is by visiting the place of business or residence and providing input and solutions to problems that are being faced in the business so that financing problems arise. Keywords: Supervision, Guidance, Murabaha, Problem Funding.